PENGARUH PSYCHOLOGICAL CAPITAL TERHADAP READINESS TO CHANGE PADA KARYAWAN PENJAGA GARDU TOL DI JABODETABEK - ahadian almizan gani; silverius y. soeharso; seta a. wicaksana; aisyah pia asrunputri (Ekonomi & Bisnis, 2019)
The government of Indonesia has started to create a policy to enact Gerakan Nasional Non- Tunai (GNNT) which was inaugurated since last 2014 and this movement started from the implementation of transaction at Jabodetabek toll road. The main purpose of this research is to evaluate the influence of psychological capital on readiness for change among toll gate guards in Jabodetabek. This research used Readiness for change scale to measure the individual readiness in facing organizational change and psychological capital questionnaire is used to measure the level of psychological capital among the respondent of the research. The respondent of this research focuses on 103 toll gate guards in Jabodetabek area. The result shows that there is a significant impact of psychological capital on readiness for change and resilience is the dimension that most significantly influences the readiness for change among the toll gate guards in Jabodetabek.Key words: Readiness for change, psychological capital, toll gate guards